Segmental vitiligo with inflammatory border. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
A 20-month-old girl was first observed for a white patch surrounded by an erythematous scaling border. The personal and family history was negative for atopy. The family history showed thyroiditis in the paternal grandfather and celiac disease in a cousin of the mother. The white patch was evident at the age of 5 months on the right abdomen with erythematous and scaling lesions during the summer (Fig. 1, inset). At the end of summer the central inflammation regressed, leaving a white patch, but an asymptomatic, peripheral inflamed edge remained. Physical examination showed on the right abdomen an achromic (Fig. 1), 5 cm wide, patch ranging from the navel up to the renal region, surrounded at its periphery by an about 3 mm rim of erythema and scaling. The final diagnosis was segmental vitiligo with inflammatory border.